The impact of COVID-19 on the quality of life of Latin Americans in New Zealand - Lopez Severiche, Alfredo; Lopez Severiche, Alfredo; Lopez Severiche, Alfredo (Corporación Universitaria Americana, 2024)
Introduction: This research explored how COVID-19 has negatively affected the quality of life for Latin Americans in New Zealand. No study has yet been conducted on this topic. Objective: This is a pilot study that describes the effects of the pandemic on the quality of life of the Latino community in that country. According to the academic literature, the concept of quality of life is broad and encompasses objective and subjective factors. Methodology: This is a qualitative study that used digital ethnography as a methodological approach. In this way, the observation of the participants through Facebook (as digital ethnography) and semi-structured interviews were used as data collection methods. Ten Latin American participants from Argentina, Colombia, Ecuador, Peru, and Venezuela participated in this study. Participants were recruited through Facebook ads. Thematic analysis was used to analyse the qualitative data produced by this research. Results: The findings of this study show that COVID-19 has not seriously affected the quality of life of the participants. Conclusions: Despite the fact that CVID-19 has somehow impacted the quality of life of Latin Americans in New Zealand, they think that their current quality of life in that country is positive, happy and pleasant.